Comparative study of oral squamous cell carcinoma over three decades at a teaching dental center in Lima, Peru - Garay Orihuela, Gianella Dayana (2025)
Objective: To compare the frequency of oral squamous cell carcinoma in an oral and maxillofacial pathology laboratory at a teaching dental center of a Peruvian university across three decades (1991 -2020). Materials and methods: A cross-sectional, observational, descriptive, retrospective study was conducted. Age group, sex, clinical manifestations, anatomical location, and decade were analyzed. Collected data were coded to preserve patient anonymity and recorded on standardized data collection form. Statistical analysis was performed using STATA 16.0 software, applying the chi-square test and Fisher's exact test, with a 95% confidence level and p < 0.05. Results: A total of 735 records were included, the mean age was 53 years. The age group with the highest frequency was 70-79 years (n = 177). The main clinical manifestations were tumors (50.75 %) and ulcers (31.68 %). The most frequent anatomical sites were the upper and lower alveolar ridge/gingiva (35.80%) and the lateral border of the tongue (23.58%). Conclusions: An increase in oral squamous cell carcinoma was observed in the most recent decade (2011-2020), with a higher prevalence in females. The most frequent anatomical sites were the upper and lower alveolar ridge/gingiva and the lateral border of the tongue. The most common clinical manifestations were tumor, ulcer, and white plaque, in that order.